2019
DOI: 10.1002/pc.25364
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of melt‐spun poly(fluorinated ethylene‐propylene)/graphene composite fibers

Abstract: The matrix of poly(fluorinated ethylene‐propylene) (FEP) was modified with graphene (GE) as filler, and then the composite fibers were prepared by melt spinning method with a twin‐screw extruder. The effects of both the draw ratio and GE content on the structures and properties of FEP/GE composite fibers were investigated. The results showed that the addition of nanoparticles reduced the crystallization of molecular chains and the orientation of crystalline units in the fibers, while the drafting and heat sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Polymers with biomedical applications such as hybrid HDPE-ultrahigh molecular weight polyethylene (UHMWPE) [69] have been modified by amine surface functionalized GO, to improve not only elastic modulus and tensile strength, but also its resistance to biodegradation, thus making the new nanocomposite a possible candidate for bone tissue applications. Polyfluorinated ethylene propylene melt-spinning fibers [70] were reported to improve their chemical resistance by the addition of graphene in a low (0.3 wt. %) proportion.…”
Section: Other Thermoplastic Matricesmentioning
confidence: 99%
“…Polymers with biomedical applications such as hybrid HDPE-ultrahigh molecular weight polyethylene (UHMWPE) [69] have been modified by amine surface functionalized GO, to improve not only elastic modulus and tensile strength, but also its resistance to biodegradation, thus making the new nanocomposite a possible candidate for bone tissue applications. Polyfluorinated ethylene propylene melt-spinning fibers [70] were reported to improve their chemical resistance by the addition of graphene in a low (0.3 wt. %) proportion.…”
Section: Other Thermoplastic Matricesmentioning
confidence: 99%
“…However, in contrast to polytetrafluoroethylene, little data on the FEP-based composites reinforced with inorganic fillers is found, all related to various carbon materials. Fillers such as graphite [ 5 , 6 ], graphene [ 7 ] and carbon nanotubes [ 8 ] were utilized in FEP-based composites. Additionally, combined carbon fillers, namely graphite + carbon nanotubes [ 9 ] and graphite + carbon fibers [ 10 ] were applied as FEP reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, combined carbon fillers, namely graphite + carbon nanotubes [ 9 ] and graphite + carbon fibers [ 10 ] were applied as FEP reinforcement. It was observed that FEP filling with carbon materials improve the processability of FEP [ 8 ] and the mechanical properties [ 7 , 8 ], and allows one to obtain composites with high electrical [ 5 , 6 , 9 ] and thermal [ 10 ] conductivities. An increase in the thermal conductivity is of particular importance for tribological applications because it can contribute to a reduction in heat development in the sliding contact area [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, fluoropolymers have always been an important research object in organic membranes, and widely used in variety of fields 13 . Polytetrafluoroethylene (PTFE), is an outstanding representative of fluoropolymers, but the “insoluble and infusible” property restricted its further development 14,15 . Under this circumstance, poly (tetrafluoroethylene‐co‐perfluoropropyl vinyl ether) (PFA)was developed in the mid‐1970s, which made up of tetrafluoroethylene (TFE) andperfluoropropyl vinyl ether (PPVE)with a mass fraction of PPVE ranging from 1–10%.…”
Section: Introductionmentioning
confidence: 99%
“…13 Polytetrafluoroethylene (PTFE), is an outstanding representative of fluoropolymers, but the "insoluble and infusible" property restricted its further development. 14,15 Under this circumstance, poly (tetrafluoroethylene-co-perfluoropropyl vinyl ether) (PFA) was developed in the mid-1970s, which made up of tetrafluoroethylene (TFE) andperfluoropropyl vinyl ether (PPVE)with a mass fraction of PPVE ranging from 1-10%. Compared to PTFE, PFA not only maintained the advantages of PTFE but also acquired good melting processing properties, which was benefited from the introduction of PPVE to confine the PTFE crystallization.…”
Section: Introductionmentioning
confidence: 99%